High strength aerogel material and method
By preparing high molecular weight linear polyimide aerogel and using supercritical drying technology, the problem of low mechanical characteristics of existing aerogel materials is solved, and aerogel materials with high mechanical strength and toughness are achieved.
Patent Information
- Application Number
- CN202380063062.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-02
- Filing Date
- 2023-08-31
- Publication Date
- 2025-04-11
AI Technical Summary
The existing aerogel materials have low mechanical properties and are difficult to meet the requirements of high Young's modulus, high compression modulus and high toughness.
High molecular weight polyimide aerogel material with linear polyimide molecules is prepared and solvents are removed by supercritical drying to form a high density aerogel structure.
The high mechanical strength and toughness of aerogel materials are achieved, specifically manifested as high Young's modulus, compression modulus and bending strength.
Smart Images

Figure CN119816542A_ABST
Abstract
Description
[0001] Priority claim
[0002] This patent application claims priority to U.S. Provisional Patent Application Serial No. 63 / 403,511, filed on September 2, 2022, entitled “HIGH STRENGTH AEROGEL MATERIAL AND METHOD,” and U.S. Provisional Patent Application Serial No. 63 / 403,225, filed on September 1, 2022, entitled “HIGH STRENGTH AEROGEL MATERIAL AND METHOD,” the entire text of which is hereby incorporated by reference herein. Technical Field
[0003] Embodiments described herein generally relate to aerogel materials. Specific examples include polyimide aerogel materials having high compression modulus, high plateau strength, and high toughness. Background Art
[0004] Polyimide materials are very useful in many engineering applications. For selected applications that benefit from light weight, high strength and low thermal conductivity properties, polymers such as polyimide can be formed into aerogel materials. However, aerogel materials can have lower mechanical property values than bulk materials. It is desirable to provide the benefits of aerogel micro / nanostructures with high levels of mechanical properties (such as high Young's modulus, high compressive stress, etc.). BRIEF DESCRIPTION OF THE DRAWINGS
[0005] Figure 1 Stress-strain graphs of polyimide materials according to some example embodiments are shown.
[0006] Figure 2A Linear polymer molecules are shown according to some example embodiments.
[0007] Figure 2B Branched polymer molecules according to some example embodiments are shown.
[0008] Figure 2C A partially crystallized polymer molecule is shown according to some example embodiments.
[0009] Figure 2D Cross-linked polymer molecules are shown according to some example embodiments.
[0010] Figure 3A Graphs showing mechanical properties of polyimide materials formed by different methods according to some example embodiments.
[0011] Figure 3BNormalized graphs of mechanical properties of polyimide materials formed by different methods are shown according to some example embodiments.
[0012] Figure 4 Graphs showing mechanical properties and other densities of polyimide aerogel materials according to some example embodiments.
[0013] Figure 5 A graph of stoichiometric balance versus viscosity is shown according to some example embodiments.
[0014] Figure 6 A graph of gel shrinkage versus viscosity is shown, according to some example embodiments.
[0015] Figure 7 A graph showing molecular weight versus bending stress for aerogel materials according to some example embodiments is shown.
[0016] Figure 8 Data showing the relationship between the amount of pyridine added and viscosity according to some example embodiments.
[0017] Fig. 9 Data showing aerogel density versus bending stress at fracture according to some example embodiments.
[0018] Fig.10 A flow chart of a method of forming an aerogel is shown, according to some example embodiments.
[0019] Fig.11 Shown are images of A) SEM (50,000X) of carbon aerogel from low viscosity 2 wt % polyimide sol; B) SEM (50,100X) of carbon aerogel from high viscosity 2 wt % polyimide sol, according to some example embodiments.
[0020] Fig.12 An XRD scattering spectrum of a polyimide aerogel according to some example embodiments is shown. The presence of many peaks confirms the semi-crystalline structure of the polyimide.
[0021] Fig.13 A Houwink plot of intrinsic viscosity versus molecular weight for polyimide sols containing DMAc solvent according to some example embodiments is shown. The linearity of the plot indicates that the polymer is primarily linear with little or no branching.
[0022] Fig.14A graph showing the relationship between the compression modulus of carbon aerogels and the modulus of polyimide aerogels according to some example embodiments. The line drawn is a visual guide. Trend is the first known report that the modulus of polymer aerogels affects the modulus of carbon aerogels. Therefore, we can reasonably expect that the novelty of polyimide strength will be observed in carbons derived from new polyimides.
[0023] Fig.15 Shows Fig.18 and Fig.19 The solid state of representative polyimide aerogel samples characterized in the table 13 CNMR spectrum (upper left), solid state 15 Plots of the N NMR spectrum (upper right), IR spectrum (middle frame), and X-ray diffraction (lower frame).
[0024] Fig.16A A plot of observed viscosity and GPC molecular weight is shown. This confirms that changes in viscosity result from changes in molecular weight and are not significantly affected by aggregation or other artifacts.
[0025] Fig. 16B A plot of log viscosity versus log molecular weight is shown. The linearity of the plot extending to high molecular weights is indicative of the linearity of the polymer, as branched materials exhibit a diminishing increase in intrinsic viscosity with increasing molecular weight.
[0026] Fig.17 Shows Fig. 20 and Fig. 22 SEM images (upper frame), Raman spectra (middle frame), and X-ray diffraction (lower frame) of a representative carbon aerogel characterized in FIG. 5 at two different magnifications.
[0027] Fig.18 General material properties of the polyimide aerogel samples are shown.
[0028] Fig.19 The mechanical properties of the polyimide aerogel samples are shown.
[0029] Fig. 20 General material properties of carbon aerogel samples from polyimide aerogels as described are shown.
[0030] Fig.21 Shown according to Fig.23 Mechanical properties of the prepared polyimide aerogel samples.
[0031] Fig. 22 Mechanical properties of carbon aerogel samples from polyimide aerogels as described are shown.
[0032] Fig.23Shown are the sol formulations and viscosities of molecular weight controlled polyimide in DMAc. DETAILED DESCRIPTION
[0033] The following description and accompanying drawings fully illustrate specific embodiments to enable those skilled in the art to practice them. Other embodiments may incorporate structural, logical, electrical, process and other changes. Portions and features of some embodiments may be included in or replace portions and features of other embodiments. The embodiments set forth in the claims encompass all available equivalents of these claims.
[0034] Aerogel
[0035] Aerogel is a solid material containing a highly porous network of micro-, meso- and macro-sized pores. Depending on the precursor materials used and the processing performed, the pores of the aerogel can typically account for more than 90% of the volume when the density of the aerogel is about 0.5 g / cc. Aerogels are generally prepared by removing solvent from the gel in a manner that minimizes or does not cause shrinkage of the gel by capillary forces at the pore walls of the gel (solid network containing the solvent). Methods for solvent removal include, but are not limited to, supercritical drying (or drying with a supercritical fluid so that the low surface tension of the supercritical fluid is exchanged with the transient solvent in the gel), exchanging solvent with a supercritical fluid, exchanging solvent with a fluid that subsequently transitions to a supercritical state, subcritical or near-critical drying, and sublimating the frozen solvent during freeze drying. See, for example, PCT Patent Application Publication No. WO2016127084A1. It should be noted that when drying under ambient conditions, gel shrinkage may occur as the solvent evaporates and a dry gel may form. Therefore, the preparation of aerogels by sol-gel methods or other polymerization methods is generally carried out in a series of steps: dissolving the solute in the solvent, adding the catalyst, forming the reaction mixture, forming the gel (which may involve additional heating or cooling), and removing the solvent by supercritical drying techniques or any other method that removes the solvent from the gel without causing shrinkage or pore collapse.
[0036] Aerogels can be formed from inorganic materials, organic materials, or mixtures thereof. When organic aerogels are formed from organic materials such as, for example, phenol, resorcinol-formaldehyde (RF), phloroglucinol-furan formaldehyde (PF), polybenzoxazine (PBO), polyacrylonitrile (PAN), polyimide (PI), polyurethane (PU), polyurea (PUA), polyamide (PA), polybutadiene, polydicyclopentadiene, and precursors or polymer derivatives thereof, the organic aerogel can be carbonized (e.g., by pyrolysis) to form a carbon aerogel, which can have different or overlapping properties (e.g., bulk density, skeleton density, porosity, pore volume, pore size distribution, morphology, etc.) depending on the precursor materials and methods used.
[0037] With respect to terms used in this disclosure, the following definitions are provided. This application will use the following terms, as defined below, unless the textual context in which the term appears requires a different meaning.
[0038] The articles "a" and "an" are used herein to refer to one or more than one (i.e., at least one) grammatical object of the article. The term "about" used throughout this specification is used to describe and explain small fluctuations. For example, the term "about" can refer to less than or equal to ±10%, or less than or equal to ±5%, such as less than or equal to ±2%, less than or equal to ±1%, less than or equal to ±0.5%, less than or equal to ±0.2%, less than or equal to ±0.1%, or less than or equal to ±0.5%. All numerical values herein are modified by the term "about", whether or not explicitly stated. Numerical values modified by the term "about" certainly also include specific numerical values. For example, "about 5.0" must include 5.0.
[0039] In the context of the present disclosure, in some examples, the term "framework" or "framework structure" refers to a network of nanoscale and / or microstructural elements (such as fibrils, pillars and / or colloidal particles) that form the solid structure of a gel or aerogel. The structural elements that constitute the framework structure have at least one characteristic dimension (e.g., length, width, diameter) of about 100 angstroms or less. In the example of aerogel that is pyrolyzed or carbonized, the term "framework" or "framework structure" can refer to an interconnected network of linear fibrils, nanoparticles, a bicontinuous network (e.g., a network that transitions between fibrils and spherical morphologies, which have aspects of both transitional structures), or a combination thereof. In some examples, linear fibrils, nanoparticles or other structural elements can be connected together (at nodes in some examples) to form a framework that defines a hole.
[0040] As used herein, the terms "aerogel" and "aerogel material" refer to a solid object, regardless of shape or size, comprising a framework of interconnected solid structures within which is integrated a corresponding network of interconnected pores, and containing a gas, such as air, as a dispersed interstitial medium. Thus, an aerogel is an open, non-fluid colloidal or polymeric network that is expanded throughout its volume by a gas and is formed by removing all of the swelling agent from a corresponding wet gel in the absence of a substantial reduction in volume or compaction of the network. Aerogels are generally characterized by the following physical and structural properties attributed to aerogels (as tested by nitrogen porosimetry and helium pycnometers): (a) an average pore diameter ranging from about 2 nm to about 100 nm; (b) a porosity of at least 60% or more, and (c) a porosity of about 50 nm according to nitrogen adsorption analysis. 2 / g or higher, such as about 100 to about 1500m 2 / g specific surface area. It is understood that the inclusion of additives, such as reinforcing materials or electrochemically active materials (e.g., silicon), may reduce the porosity and specific surface area of the resulting aerogel composite. Densification may also reduce the porosity of the resulting aerogel composite. The aerogel materials of the present disclosure include any aerogel that meets the critical elements listed in the previous paragraphs.
[0041] Thus, aerogel materials of the present disclosure include any aerogel or other open-cell material that meets the defining elements listed in the preceding paragraph, including materials that may otherwise be classified as xerogels, cryogels, bigels, microporous materials, and the like.
[0042] As used herein, the term "xerogel" refers to a gel comprising an open non-fluid colloid or polymer network formed by removing all swelling agents from the corresponding gel without taking any precautions to avoid a substantial reduction in volume or to hinder compaction. Xerogels have a viscosity of 0-700 m / s as measured by nitrogen adsorption analysis. 2 / g of surface area.
[0043] As used herein, the term "gelation" or "gel transition" refers to the formation of a wet gel by a polymer system. At a time point defined as the "gel point", the sol loses fluidity. In this context, gelation starts from the initial sol state, passes through a high viscosity dispersion state, until the dispersion state solidifies and the sol gels (gel point), thereby producing a wet gel. The amount of time required for the reaction solution to be converted into a gel in a form that is no longer flowable is called the "phenomenal gelation time". Formally, the gelation time is measured using rheology. Near the gel point, the elastic properties of the solid gel begin to dominate over the viscous properties of the fluid sol. The formal gelation time is the time when the real part and the imaginary part of the complex modulus of the sol in the gelation intersect. The change of these two moduli over time is monitored using a rheometer. The time is counted from the moment when the last component of the sol is added to the solution. See, for example, the discussion of gelation in the following literature: HH Winter'"Can the Gel Point of a Cross-linking Polymer Be Detected by the G'-G'"Crossover? '"Polym.Eng.Sci.,1987,27,1698–1702; S.-Y.Kim, D.-G.Choi and S.-M.Yang'"Rheological analysis of the gelation behavior of tetraethylorthosilane / vinyltriethoxysilane hybrid solutions'"Korean J. Chem. Eng., 2002, 19, 190–196; and M. Muthukumar'"Screening effect on viscoelasticity near the gel point'" Macromolecules, 1989, 22, 4656–4658.
[0044] As used herein, the term "wet gel" refers to a gel in which the mobile interstitial phase within the network of interconnected pores is primarily composed of a liquid phase (such as a conventional solvent or water), a liquefied gas (such as liquid carbon dioxide), or a combination thereof. Aerogels typically require initial production of a wet gel, followed by processing and extraction to replace the mobile interstitial liquid phase in the gel with air or another gas. Examples of wet gels include, but are not limited to, alcohol gels, hydrogels, keto gels, carbonogels, and any other wet gels known to those skilled in the art.
[0045] Aerogels as disclosed herein have a density. As used herein, the term "density" refers to a measurement of the mass per unit volume of an aerogel material or composition. The term "density" generally refers to the true density or skeletal density of an aerogel material, as well as the bulk density of an aerogel composition. Density is generally measured as kg / m 3 or g / cm 3 The skeletal density of the polyimide or carbon aerogel can be determined by methods known in the art, including but not limited to helium pycnometer determination. The bulk density of the polyimide or carbon aerogel can be determined by methods known in the art, including but not limited to: Standard Test Method for Dimensions and Density of Preformed Block and Board-Type Thermal Insulation (ASTM C303, ASTM International, West Conshohocken, Pa.); Standard Test Methods for Thickness and Density of Blanket or Batt Thermal Insulations (ASTM C167, ASTM International, West Conshohocken, Pa.); or Determination of the apparent density of preformed pipe insulation (ISO 18098, International Organization for Standardization, Switzerland). In the context of the present disclosure, unless otherwise stated, density measurements are obtained according to ASTM C167 standard. In some embodiments, the polyimide or carbon aerogel as disclosed herein has a density of about 0.01 to about 0.3 g / cm 3 The bulk density.
[0046] Aerogels as disclosed herein have a pore size distribution. As used herein, the term "pore size distribution" refers to the statistical distribution or relative amount of each pore size within the sample volume of a porous material. A narrow pore size distribution refers to a relatively large proportion of pores being in a narrow pore size range. In some embodiments, a narrow pore size distribution may be desirable when, for example, optimizing the number of pores that can surround an electrochemically active material and maximizing the use of available pore volume. On the contrary, a wide pore size distribution refers to a relatively small proportion of pores being in a narrow pore size range. Therefore, the pore size distribution is usually measured as a function of pore volume and recorded as the unit size of the half-maximum full width of the main peak in the pore size distribution diagram. The pore size distribution of a porous material can be determined by methods known in the art, such as, but not limited to, surface area, skeletal density, and porosity determination, from which the pore size distribution can be calculated. Suitable methods for determining such features include, but are not limited to, gas adsorption / desorption (e.g., nitrogen) measurements, helium pycnometer determination, mercury porosimetry, etc. Unless otherwise stated, the pore size distribution measurements reported herein are obtained by nitrogen adsorption analysis. In certain embodiments, the polyimides or carbon aerogels of the present disclosure have a relatively narrow pore size distribution.
[0047] The aerogel materials or compositions of the present disclosure may have a pore size at the maximum peak in a distribution of about 150 nm or less, 140 nm or less, 130 nm or less, 120 nm or less, 110 nm or less, 100 nm or less, 90 nm or less, 80 nm or less, 70 nm or less, 60 nm or less, 50 nm or less, 40 nm or less, 30 nm or less, 20 nm or less, 10 nm or less, 5 nm or less, 2 nm or less, or in a range between any two of these values.
[0048] The aerogels disclosed herein have a pore volume. As used herein, the term "pore volume" refers to the total volume of pores within a sample of a porous material. Pore volume is specifically measured as the volume of the void spaces within the porous material and is usually reported as cubic centimeters per gram (cm 3 / g or cc / g). The pore volume of the porous material can be determined by methods known in the art, such as, but not limited to, surface area and porosity analysis (e.g., nitrogen porosimetry, mercury porosimetry, helium pycnometer measurement, etc.). In certain embodiments, the polyimide or carbon aerogel of the present disclosure has a relatively large pore volume of about 1 cc / g or more, 1.5 cc / g or more, 2 cc / g or more, 2.5 cc / g or more, 3 cc / g or more, 3.5 cc / g or more, 4 cc / g or more, or in a range between any two of these values. In other embodiments, the polyimide or carbon aerogel and xerogel of the present disclosure has a pore volume of about 0.03cc / g or more, 0.1cc / g or more, 0.3cc / g or more, 0.6cc / g or more, 0.9cc / g or more, 1.2cc / g or more, 1.5cc / g or more, 1.8cc / g or more, 2.1cc / g or more, 2.4cc / g or more, 2.7cc / g or more, 3.0cc / g or more, 3.3cc / g or more, 3.6cc / g or more, or in a range between any two of these values.
[0049] Generally, the formation of aerogel includes drying wet gel in one or more stages. In some embodiments, wet gel (polyamic acid or polyimide) is aged. After any aging, it is possible to collect (for example, demoulding) and clean the obtained wet gel material or to carry out solvent exchange in a suitable auxiliary solvent to replace the main reaction solvent (i.e. water) present in the wet gel. Such auxiliary solvents can be straight-chain alcohols with 1 or more aliphatic carbon atoms, glycols with 2 or more carbon atoms, or branched alcohols, cyclic alcohols, alicyclic alcohols, aromatic alcohols, polyols, ethers, ketones, cyclic ethers or their derivatives. In some embodiments, auxiliary solvents are water, C1 to C3 alcohols (for example, methanol, ethanol, propanol, isopropanol), acetone, tetrahydrofuran, ethyl acetate, acetonitrile, supercritical fluid carbon dioxide (CO2) or their combination. In some embodiments, auxiliary solvents are ethanol.
[0050] Once the wet gel has been formed and processed, the liquid phase (e.g., polyamic acid or polyimide) of the wet gel can then be at least partially extracted from the wet gel material using an extraction method (including processing and extraction techniques) to form an aerogel material (i.e., "drying"). Liquid phase extraction plays an important role in the properties (such as porosity and density) and related properties (such as thermal conductivity) of engineered aerogels, among other factors. Typically, an aerogel is obtained when the liquid phase is extracted from the wet gel in a manner that causes a low shrinkage of the porous network and framework of the wet gel. Various techniques can be used to dry the wet gel to provide an aerogel or a xerogel. In an exemplary embodiment, the wet gel material can be dried at ambient pressure, under vacuum (e.g., by freeze drying), under subcritical conditions, or under supercritical conditions to form a corresponding dry gel (e.g., an aerogel, such as a xerogel).
[0051] In some embodiments, it may be desirable to fine-tune the surface area of the dried gel. If fine-tuning of the surface area is desired, the aerogel can be converted in whole or in part into a xerogel with various porosities. The high surface area of the aerogel can be reduced by forcing some of the pores to collapse. This can be accomplished, for example, by immersing the aerogel in a solvent such as ethanol or acetone for a period of time or by exposing the aerogel to solvent vapors. The solvent is then removed by drying at ambient pressure.
[0052] Aerogels are typically formed by removing a liquid mobile phase from a wet gel material at a temperature and pressure close to or above the critical point of the liquid mobile phase. Once the critical point is reached (near critical) or exceeded (supercritical; that is, the pressure and temperature of the system are equal to or above the critical pressure and critical temperature, respectively), a new supercritical phase appears in the fluid, which is different from the liquid or vapor phase. The solvent can then be removed without introducing a liquid-vapor interface, capillary forces, or any related mass transfer limitations typically associated with a receding liquid-vapor boundary. In addition, the supercritical phase is typically more miscible with organic solvents and therefore has better extraction capabilities. Cosolvents and solvent exchange are also commonly used to optimize supercritical fluid drying processes.
[0053] If evaporation or extraction occurs below the supercritical point, the capillary forces generated by the evaporation of the liquid can cause shrinkage and pore collapse within the gel material. Maintaining the mobile phase near or above the critical pressure and temperature during the solvent extraction process can reduce the negative effects of such capillary forces. In certain embodiments of the present disclosure, the use of near-critical conditions just below the critical point of the solvent system can allow the production of aerogels or compositions with sufficiently low shrinkage to produce a commercially viable final product.
[0054] The wet gel can be dried using various techniques to provide an aerogel. In exemplary embodiments, the wet gel material can be dried under ambient pressure, subcritical conditions, or supercritical conditions.
[0055] Both room temperature and high temperature methods can be used to dry the gel material at ambient pressure. In some embodiments, a slow ambient pressure drying method can be used, wherein the wet gel is exposed to air in an open container for a period of time sufficient to remove the solvent, e.g., a period of time ranging from a few hours to a few weeks, depending on the solvent, the amount of wet gel, the exposed surface area, the size of the wet gel, etc.
[0056] In another embodiment, the wet gel material is dried by heating. For example, the wet gel material can be heated in a convection oven for a period of time to evaporate most of the solvent (e.g., ethanol). After partial drying, the gel can be placed at ambient temperature for a period of time, such as several hours to several days, to completely dry. This drying method can produce a xerogel.
[0057] In some embodiments, the wet gel material is dried by freeze drying. "Freeze drying" or "lyophilization" means a low temperature method for removing solvents, which involves freezing the material (e.g., wet gel material), reducing the pressure, and then removing the frozen solvent by sublimation. Since water is an ideal solvent to be removed by freeze drying, and water is a solvent in the method disclosed herein, freeze drying is particularly suitable for forming aerogels from the disclosed polyimide wet gel material. This drying method produces cold gels, which may be very similar to aerogels.
[0058] Both supercritical and subcritical drying can be used to dry the wet gel material. In some embodiments, the wet gel material is dried under subcritical or supercritical conditions. In an exemplary embodiment of supercritical drying, the gel material can be placed in a high pressure container to extract the solvent with supercritical CO2. After removing the solvent (e.g., ethanol), the container can be kept above the critical point of CO2 for a period of time, such as about 30 minutes. After supercritical drying, the container is depressurized to atmospheric pressure. Typically, aerogels are obtained by this method.
[0059] In an exemplary embodiment of subcritical drying, the gel material is dried using liquid CO2 at a pressure in the range of about 800 psi to about 1200 psi at room temperature. This operation is faster than supercritical drying; for example, the solvent (e.g., ethanol) can be extracted in about 15 minutes. Typically, aerogels are obtained by this method.
[0060] Several additional aerogel extraction techniques are known in the art, including a range of different approaches to drying aerogels using supercritical fluids, and ambient drying techniques. For example, Kistler (J. Phys. Chem. (1932) 36: 52-64) describes a simple supercritical extraction method in which the gel solvent is maintained above its critical pressure and temperature, thereby reducing evaporative capillary forces and maintaining the structural integrity of the gel network. U.S. Patent No. 4,610,863 describes an extraction method in which the gel solvent is exchanged with liquid carbon dioxide and then extracted under conditions in which the carbon dioxide is in a supercritical state. U.S. Patent No. 6,670,402 teaches the extraction of a liquid phase from a gel via rapid solvent exchange by injecting supercritical (rather than liquid) carbon dioxide into an extractor that has been preheated and pre-pressurized to substantially supercritical conditions or higher, thereby producing an aerogel. U.S. Patent No. 5,962,539 describes a method for obtaining an aerogel from a polymer material in the form of a sol-gel in an organic solvent by exchanging the organic solvent for a fluid having a critical temperature below the decomposition temperature of the polymer composition, and then supercritically extracting the fluid from the sol-gel. U.S. Patent No. 6,315,971 discloses a method for producing a gel composition, the method comprising: drying a wet gel containing gel solids and a desiccant under drying conditions sufficient to reduce shrinkage of the gel during drying to remove the desiccant. U.S. Patent No. 5,420,168 describes a method whereby resorcinol / formaldehyde aerogels can be made using a simple air drying procedure. U.S. Patent No. 5,565,142 describes a drying technique in which the gel surface is modified to be more solid and more hydrophobic so that the gel framework and pores can resist collapse during ambient drying or subcritical extraction. Other examples of extracting a liquid phase from an aerogel material can be found in U.S. Patent Nos. 5,275,796 and 5,395,805.
[0061] In some embodiments, the liquid phase is extracted from the wet gel using supercritical conditions of carbon dioxide, including, for example: first, fully exchanging the main solvent present in the gel pore network with liquid carbon dioxide; and then heating the wet gel (usually in an autoclave) above the critical temperature of carbon dioxide (about 31.06°C), and increasing the pressure of the system to a pressure greater than the critical pressure of carbon dioxide (about 1070psig). The pressure around the gel material can be slightly fluctuated to facilitate the removal of supercritical carbon dioxide fluid from the gel. Carbon dioxide can be recycled through the extraction system to facilitate the continuous removal of the main solvent from the wet gel. Finally, the temperature and pressure are slowly restored to ambient conditions to produce dry aerogel material. Carbon dioxide can also be pre-processed into a supercritical state before being injected into the extraction chamber. In other embodiments, any suitable mechanism (such as changing the pressure, timing and solvent discussed above) can be used for extraction.
[0062] For ease of illustration, the next section describes the composition, formation, and morphology of polyimide aerogels. It will be appreciated that aerogels may be synthesized using many different precursors and techniques. In addition, it will be appreciated that processing parameters associated with these different aerogel compositions may be modified to achieve a specific morphology.
[0063] The method of forming a polyimide gel or aerogel includes a method of preparing a polyimide gel by condensing a diamine and a tetracarboxylic dianhydride in an organic solvent solution to form a polyamic acid and dehydrating the polyamic acid. See, for example, U.S. Patent Nos. 7,071,287 and 7,074,880 to Rhine et al., and U.S. Patent Application Publication No. 2020 / 0269207 to Zafiropoulos et al.
[0064] According to certain embodiments, the production of the aerogel comprises the steps of: i) forming a solution containing a gel precursor; ii) forming a gel from the solution; and iii) extracting the solvent from the gel material to obtain a dry aerogel material.
[0065] In one example, the polyimide aerogel is formed by combining at least one diamine and at least one dianhydride in one or more common polar aprotic solvents. Additional details on the formation of polyimide gels / aerogels can be found in: U.S. Pat. Nos. 7,074,880 and 7,071,287 to Rhine et al.; U.S. Pat. No. 6,399,669 to Suzuki et al.; U.S. Pat. No. 9,745,198 to Leventis et al.; Leventis et al., Polyimide Aerogels by Ring-Opening Metathesis Polymerization (ROMP), Chem. Mater. 2011, 23, 8, 2250-2261, etc., each of which is incorporated herein by reference in its entirety.
[0066] In certain examples, the present disclosure relates to the formation and use of nanoporous carbon-based scaffolds or structures (eg, carbon aerogels) as electrode materials.
[0067] In addition, it is contemplated herein that the nanoporous carbon-based scaffold or structure, in particular the carbon aerogel, can be in the form of a monolithic structure. When the carbon aerogel is essentially a monolithic material, the carbon aerogel eliminates the need for any binder; in other words, the air cathode can be binder-free. As used herein, the term "monolithic material" refers to an aerogel material in which the majority (by weight) of the aerogel contained in the aerogel material or composition is in the form of a singular, continuous, interconnected aerogel nanostructure. Monolithic aerogel materials include aerogel materials that are initially formed to have a singular, interconnected gel or aerogel nanostructure, but can subsequently be broken, fractured or split into non-singularized aerogel nanostructures.
[0068] Monolithic aerogel materials are distinguished from particulate aerogel materials. The term "particulate aerogel material" refers to an aerogel material in which the majority (by weight) of the aerogel contained in the aerogel material is in the form of particulates, particles, granules, beads or powders, which can be combined together (i.e., via a binder, such as a polymer binder), or compressed together but lack interconnected aerogel nanostructures between individual particles. In general, this form of aerogel material will be referred to as having a powder or particulate form (as opposed to a monolithic form). It should be noted that although the individual particles of the powder have a singularized structure, the individual particles are not considered monolithic in this article. Integrating aerogel powder into an electrochemical cell typically involves preparing a paste or slurry from the powder, casting and drying onto a substrate, and may optionally include calendering.
[0069] Within the context of the present disclosure, the term "binderless" or "binder-free" (or its derivatives) refers to a material that is substantially free of a binder or adhesive used to hold the material together. For example, a monolithic nanoporous carbon material is binder-free because its framework is formed as a unitary, continuous interconnected structure. The advantages of being binder-free include avoiding any effects of the binder, such as effects on conductivity and pore volume. On the other hand, aerogel particles require a binder to be held together to form a larger functional material; such a larger material is not considered herein as a monolith. In addition, the term "binder-free" does not exclude all uses of binders. For example, according to the present disclosure, a monolithic aerogel can be fastened to another monolithic aerogel or non-aerogel material by arranging a binder or adhesive on a major surface of the aerogel material. In this way, the binder is used to create a laminated composite and provide electrical contact with the collector, but the binder does not have the function of maintaining the stability of the monolithic aerogel framework itself.
[0070] According to the present disclosure, nanoporous carbon (such as carbon aerogel) can be formed by any suitable organic precursor material. Examples of such materials include, but are not limited to, RF, PF, PI, polyamide, polyoxyalkylene, polyurethane, polyacrylonitrile, cresol formaldehyde, phenol-furfural, polyisocyanate, polyvinyl alcohol dialdehyde, polyisocyanurate, various epoxy resins, chitosan, and combinations and derivatives thereof. Any precursor of these materials can be used to create and use the resulting material. In some instances, carbon aerogel is formed by pyrolysis / carbonized polyimide-based aerogel (i.e., polymerization of polyimide). Even more specifically, polyimide-based aerogel can be produced using one or more methods described in U.S. Patent Nos. 7,071,287 and 7,074,880 of Rhine et al. (e.g., by imidization of poly (amide) acid and using supercritical fluid to dry the resulting gel). Other suitable methods for producing polyimide aerogels (and carbon aerogels derived therefrom) are also contemplated herein, such as those described in the following references: U.S. Pat. No. 6,399,669 to Suzuki et al.; U.S. Pat. No. 9,745,198 to Leventis et al.; Leventis et al., Polyimide Aerogels by Ring-Opening Metathesis Polymerization (ROMP), Chem. Mater. 2011, 23, 8, 2250-2261; Leventis et al., Isocyanate-Derived Organic Aerogels: Polyureas, Polyimides, Polyamides, MRS Proceedings, 1306 (2011), Mrsf10-1306-bb03-01.doi:10.1557 / opl.2011.90; Chidambareswarapattar et al., One-step room-temperature synthesis of fibrous polyimide aerogels from anhydrides and isocyanates and conversion to isomorphic carbons, J.Mater.Chem., 2010, 20, 9666–9678; Guo et al., Polyimide Aerogels Cross-Linked through Amine Functionalized Polyoligomeric Silsesquioxane, ACS Appl.Mater.Interfaces2011,3,546–552; Nguyen et al., Development of High Temperature, Flexible Polyimide Aerogels, American Chemical Society, procedures published 2011; Meador et al., Mechanically Strong, Flexible Polyimide Aerogels Cross-Linked with Aromatic Triamine, ACSAppl.Mater.Interfaces, 2012, 4(2), pp 536–544; Meador et al., Polyimide Aerogels with Amide Cross-Links: A Low Cost Alternative for Mechanically Strong PolymerAerogels, ACS Appl.Mater.Interfaces 2015, 7, 1240-1249; Pei et al., Preparation and Characterization of Highly Cross-Linked Polyimide Aerogels Based on PolyimideContaining Trimethoxysilane Side Groups,Langmuir 2014,30,13375-13383. The resulting polyimide aerogel is then pyrolyzed to form a polyimide-derived carbon aerogel.
[0071] The carbon aerogel of the present disclosure may include a carbon aerogel formed from any one or more of the following aerogels: a polyimide-derived carbon aerogel; a polybenzodiazine-derived carbon aerogel; a polybenzoxazine-derived carbon aerogel; a polyamide-derived carbon aerogel; a polyimide-derived carbon aerogel, wherein the polyimide aerogel is synthesized via an isocyanate route; a polyacrylonitrile-derived carbon aerogel; a polyurea-derived aerogel; a phenol-derived carbon aerogel; a phenol-formaldehyde-derived carbon aerogel; a phloroglucinol-terephthalaldehyde-derived carbon aerogel; and a phloroglucinol-formaldehyde-derived carbon aerogel.
[0072] In some examples, the carbon aerogels of the present disclosure can have a residual nitrogen content of at least about 14 wt %. For example, the carbon aerogels can have a residual nitrogen content of at least about 0.1 wt %, at least about 0.5 wt %, at least about 1 wt %, at least about 2 wt %, at least about 3 wt %, at least about 4 wt %, at least about 5 wt %, at least about 6 wt %, at least about 7 wt %, at least about 8 wt %, at least about 9 wt %, at least about 10 wt %, at least about 14 wt %, or a range between any two of these values.
[0073] In examples of the present disclosure, the dried polymer aerogel composition can be subjected to a treatment temperature of 200°C or more, 400°C or more, 600°C or more, 800°C or more, 1000°C or more, 1200°C or more, 1400°C or more, 1600°C or more, 1800°C or more, 2000°C or more, 2200°C or more, 2400°C or more, 2600°C or more, 2800°C or more, or in a range between any two of these values, to carbonize the organic (e.g., polyimide) aerogel. In an exemplary embodiment, the dried polymer aerogel composition can be subjected to a treatment temperature in the range of about 1000°C to about 1100°C, such as at about 1050°C. Without being bound by theory, it is contemplated herein that the conductivity of the aerogel composition increases with increasing carbonization temperature. In some examples, some compositions or aerogel types will become conductive when carbonized above a threshold carbonization temperature (eg, above 400° C., above 500° C., above 600° C.).
[0074] Young's modulus can be measured by methods known in the art, such as, but not limited to, Standard Test Practice for Instrumented Indentation Testing (ASTM E2546, ASTM International, West Conshocken, PA); or Standardized Nanoindentation (ISO 14577, International Organization for Standardization, Switzerland). Unless otherwise stated, in the context of the present disclosure, the measurement of Young's modulus is obtained according to ASTM E2546 and ISO 14577. In certain embodiments, the carbonized aerogel material or composition of the present disclosure has a Young's modulus of about 0.2 GPa or greater, 0.4 GPa or greater, 0.6 GPa or greater, up to about 1 GPa, or in a range between any two of these values.
[0075] In the context of the present disclosure, the term "pillar width" refers to the average diameter of the nanopillars, nanorods, nanofibers or nanofilaments that form an aerogel having a fibril morphology. It can be recorded as any unit length, such as μm or nm. The pillar width can be determined by methods known in the art, including, for example, but not limited to scanning electron microscopy image analysis. In the context of the present disclosure, unless otherwise stated, the measured values of the pillar width are obtained according to this method. The aerogel material or composition of the present disclosure can have a pillar width of about 10nm or less, 9nm or less, 8nm or less, 7nm or less, 6nm or less, 5nm or less, 4nm or less, 3nm or less, 2nm or less, or in a range between any two of these values. Smaller pillar widths (such as those in the range of about 2-5nm) allow a larger number of pillars to be present in the network, and thereby contact the electrochemically active material, thereby allowing more electrochemically active materials to be present in the composite material. This will increase conductivity and mechanical strength.
[0076] In the context of the present disclosure, the term "fibril morphology" refers to the structural morphology of nanoporous carbon (e.g., aerogel), which includes pillars, rods, fibers or filaments. For example, the choice of solvent, such as dimethylacetamide (DMAC), can affect the generation of this morphology. Further, when the carbon aerogel is derived from polyimide, the crystalline polyimide is produced by the polyimide forming a linear polymer. It is surprisingly observed that some examples of the present disclosure include fibril morphology as an interconnected polymer structure, in which long linear structures are expected based on the known behavior of the polyimide precursor. In contrast, the product form of nanoporous carbon can alternatively be a granular substance in nature, or a powder, in which the fibril morphology of the carbon aerogel still exists. In some instances, the fibril morphology can provide certain benefits relative to the granular substance morphology, such as mechanical stability / strength and conductivity, especially when the nanoporous carbon is implemented in a specific application, such as as an anode material in a LIB. It is noteworthy that this fibril morphology can be found in both monolithic and powder forms of nanoporous carbon; in other words, monolithic carbon can have a fibril morphology and aerogel powders / particles can have a fibril morphology. Furthermore, when the nanoporous carbon material contains additives such as silicon or other additives, the inherent fibril nanostructure of the carbon material is retained and acts as a bridge between the additive particles.
[0077] As noted above, aerogel materials formed with a polyimide matrix can form many different microstructures / nanostructures. In addition, many different additional components and / or reinforcing materials can be added to modify the polyimide aerogel. In one example, the disclosed polyimide aerogel includes a range of 400-730 m2 / g of BET surface area. In one example, the disclosed polyimide aerogel includes a porosity ranging from 80-96%. In one example, the disclosed polyimide aerogel includes an average pore diameter ranging from 8-30 nm.
[0078] Example Implementation and Experimental Results
[0079] Figure 1 A stress-strain curve 100 of an aerogel material according to one example is shown. A close-up view 110 of the stress-strain curve 100 shows a Young's modulus line 112, whose slope is equal to the Young's modulus of the measured polymer. A plateau modulus line 114 is also shown. Since the plateau modulus line 114 is approximately flat, the stress value (Y-axis) of the plateau modulus line 114 represents the plateau stress or yield stress of the measured polymer.
[0080] Figure 2A An example of a linear polymer molecule 200 is shown. In one example, the linear polymer molecule 200 includes a polyimide molecule. Figure 2A The figure shows that the linear polymer molecule 200 comprises a single polymer chain that is not branched or cross-linked with other polymer molecules. As shown, the term "linear polymer molecule" does not require that the polymer molecule has a straight line conformation. Figure 2A The unbranched and uncrosslinked molecules 200 shown in will likely be distorted into a long, randomly oriented conformation. In one example of the polyimide polymer described in the present disclosure, the length of the linear polymer molecules 200 and the amount of entanglement with other adjacent linear polymer molecules play an important role in determining the mechanical properties of the bulk polymer. In one example, the bulk polymer formed of the linear polymer molecules as described is formed into a matrix of an aerogel structure, wherein the matrix contains pores.
[0081] and Figure 2A Compared with linear polymer molecules, Figure 2B A branched polymer molecule 210 is shown. In one example, a first polymer chain 212 branches into one or more sub-chains 214 at one or more branching locations 216. The complexity of the branched polymer molecule 210 provides many potentially desirable material properties, such as high modulus. However, the branched polymer molecule 210 may have negative properties such as reduced toughness. Branched polymers may also require additional cost and / or processing complexity to synthesize.
[0082] and Figure 2A Compared with linear polymer molecules, Figure 2C Crosslinked polymer molecules 220 are shown. In one example, a first polymer chain 222 is chemically bonded to another polymer chain 224 at one or more crosslinking sites 226. Figure 2BSimilar to the branched polymer molecule example 210, the complexity of the cross-linked polymer molecule 220 provides many potentially desirable material properties, such as high modulus.
[0083] Figure 2D A partially crystallized polymer molecule 230 is shown. In one example, the partially crystallized polymer molecule 230 includes a polyimide molecule. In one example, the partially crystallized polymer molecule 230 includes Figure 2A Described linear polymer molecules without branches or crosslinks. Many amorphous regions 232 are shown, and many crystalline regions 234 are shown. Variables such as the number and size of crystalline regions 234 can affect the mechanical properties of the bulk polymer. As noted above, a single linear polymer molecule with sufficient molecular weight (related to the length of the polymer chain) can include both crystalline regions 234 and amorphous regions 232. Many polymer molecules can also interact with each other and provide both crystalline regions 234 and amorphous regions 232. In partially crystalline polymers, crystalline regions 234 can provide a pinning effect for the movement of polymer molecules. This can provide desired material properties, such as high modulus and / or compressive strength, without sacrificing toughness.
[0084] In one example, as described in the examples below, the high molecular weight of the linear polyimide molecules promotes a certain amount of crystallinity. Figure 2B and 2C The branched and / or cross-linked molecules described in the above may limit or prevent the formation of crystalline regions. In one example, linear polyimide molecules with a molecular weight greater than 10,000 g / mol provide sufficient crystalline regions to provide enhanced mechanical properties, as described in the examples below. In one example, linear polyimide molecules with a molecular weight greater than 10,000 g / mol enhance mechanical properties through molecular entanglement.
[0085] Figure 3A A graph 300 of the compression modulus and monomer addition order of many different polyimide aerogel samples synthesized under three different solution concentrations (2%, 5% and 10% solid) is shown. The sample is formed by reacting pyromellitic dianhydride (PMDA) with p-phenylenediamine (PDA) to form polyamic acid molecules. The polyamic acid molecules are then chemically imidized by adding pyridine and acetic anhydride to the polymer solution, thereby producing a polyimide that retains the polyamic acid polymer chain length and branching degree. In an example, the polyimide molecules are linear polyimide molecules. Figure 3A The method of dissolving one or more components (PMDA, PDA) in dimethylacetamide (DMA) is shown. c In a type of polymerization called “slow normal” (asterisk), PMDA was first dissolved in DMA. cIn the embodiment of the present invention, the PMDA (diamond) is stirred for 20-30 minutes. PDA is added later and placed overnight for polymerization. Alternatively, PDA can also be added after stirring PMDA (diamond) for one minute, which is called the "fast normal" process. As shown in the figure, the slow normal process will result in a lower Young's modulus, while the fast normal process will result in an increase in Young's modulus.
[0086] By first dissolving PDA in DMA c In the process of adding PMDA in the first step and then adding PMDA later, the reaction between PMDA and PDA occurs preferentially over PMDA degradation. This method (PDA then PMDA) produces longer (higher molecular weight) linear polyimide molecules with improved mechanical properties compared to the "slow normal" method and comparable properties to the "fast normal" method. The PDA then PMDA method is less sensitive to mixing time, as high modulus can be achieved with a mixing time of 15 minutes.
[0087] Figure 3B A graph 350 is shown including the compression modulus normalized to the bulk density of the aerogel. Figure 3B As indicated by the data, the improvement of mechanical properties, especially the improvement of compression modulus, is determined by the structural factors of polyimide aerogels and is not just the result of changing the aerogel density.
[0088] Figure 4 A plot of the compression modulus 400 and compressive yield stress 410 versus aerogel bulk density for a number of different polyimide aerogel samples is shown. The aerogel samples were synthesized at solution concentrations between 2% and 10% solids. Bulk densities between 0.05 and 0.35 g / cm 3 Young's modulus data 402 between 0.05 and 0.35 g / cm. The properties of the polyimide aerogel material formed using the methods described in the present disclosure show very high Young's modulus at a given density range. 3 The compressive yield stress data between 412. The polyimide aerogel material having a polyimide matrix composed of linear polyimide molecules has a bulk density of 0.05 to 0.35 g / cm 3 The polyimide aerogel material having a polyimide matrix composed of linear polyimide molecules also exhibits a compressive yield stress of up to 6.3 MPa when the bulk density is between 0.05 and 0.35 g / cm 3 It exhibits a compression modulus as high as 254MPa.
[0089] Figure 5 A graph of plateau stress 500 is shown with data for a number of samples, including the current samples discussed and claimed in this disclosure, as well as samples from the current literature. Figure 5As shown in , the inventive samples exhibit a trend 502 that has an improved plateau stress at a given packing density compared to trend line 504 from the current literature.
[0090] Figure 6 A graph 600 is shown of the viscosity of a solution of 5% polyamic acid in DMAc versus the stoichiometric balance between PMDA and PDA (r = mol PMDA / mol PDA) according to some example embodiments. As r (x-axis) approaches 1.00, the reaction of PDMA approaches a complete 1:1 reaction with PDA, resulting in a higher degree of polymerization, as described by the Carothers equation. As indicated in graph 600, the viscosity of the polymerized gel increases as the stoichiometric balance approaches 1.00. Figure 6 As shown in Figure 1, PDA was first dissolved in DMA c The "reverse" process of adding PMDA and then producing a much higher viscosity. In one example, the higher viscosity can be attributed to the formation of higher molecular weight linear polymers.
[0091] Figure 7 A graph 700 of the weight average molecular weight versus bending stress of a polyimide aerogel material as described is shown. Higher molecular weight samples are shown to provide higher bending stress at break. In one example, as discussed above, higher viscosity gels indicate higher molecular weight linear molecules. Figure 7 Molecular weight is directly related to one example mechanical property (flexural stress at break). Other mechanical properties such as compression modulus and plateau stress are expected to follow similar trends.
[0092] Figure 8 Data 800 showing the viscosity of polyamic acid solutions (sol) before and after polymerization and the presence of pyridine. Three polymer solution solids concentrations are shown. The Y-axis in the figure indicates the viscosity of the resulting polymer solution, which is related to improved mechanical properties as described above. Pyridine was added to PDA and DMA before the addition of PDMA during the formation of polyimide aerogels. c The viscosity of the resulting gel can be increased in the presence of pyridine. At high concentrations, pyridine significantly helps to achieve higher molecular weights because it increases the solubility of PDA, allowing for a better PDA / PMDA stoichiometry during polymerization. Low concentrations (less than 5% solids) show that polymerization with pyridine results in lower viscosities, leading to lower molecular weights.
[0093] Fig. 9 The relationship between the bending stress at the time of aerogel fracture and the timing of pyridine addition is shown in data 900. Figure 8As shown in , above the midpoint 902 of 5% solid polymer concentration, adding pyridine to the reaction prior to polymerization can provide improved mechanical properties, such as the bending stress at break plotted. The improvement is shown at 904 on the graph 900. Below the midpoint 902, adding pyridine reduces the bending stress at break.
[0094] Fig.10 An example flow chart of a method for forming a polyimide aerogel is shown. In operation 1002, PMDA and PDA are polymerized to form a polyamic acid matrix having a molecular weight greater than 10,000 g / mol. In operation 1004, the polyamic acid matrix is chemically imidized to produce a gelled polyimide matrix without chemical crosslinking. In operation 1006, the solvent is removed from the gelled polyimide matrix to form a polyimide aerogel.
[0095] General Synthesis Methods
[0096] For illustrative purposes, this describes Fig.18 and 19 Table 1 shows the synthesis procedure of a representative polyimide sample. In this sample, T d was set to be equal to 0.02, the molar ratio of pyridine to PMDA was set to 1.0, and the ratio of acetic anhydride to PMDA was set to 4.3. To this end, 1,4-phenylenediamine (PDA; 18.23 g) was dissolved in 2667 mL of N, N-dimethylacetamide (DMAc) in a 4000 mL beaker. After 15 minutes, solid pyromellitic dianhydride (PMDA; 36.77 g) was added to the solution. The solution was stirred overnight at room temperature using a Caframo mechanical stirrer equipped with a 2-inch radius propeller shaft. At the end of this period, 1.0 equivalents of pyridine (13.33 g, 13.57 mL) were added to the solution. After mixing for 2 minutes, 4.3 equivalents of acetic anhydride (74.00 g, 68.52 mL) were added to the solution. The target density T of the resulting sol d 0.02g / cm 3 The new solution was dispensed into cylindrical polypropylene syringe molds and the solution was allowed to gel. The syringe molds were covered with 2 layers of Parafilm TM Cover, and allow the syringe mold to age for 24 hours at room temperature. In selected examples, dianhydride is selected from a list including but not limited to PMDA, BTDA, BPADA, BPDA, ODPA, DSDA and 6FDA. In selected examples, diamine is selected from a list including but not limited to PDA, meta-PDA, ODA, BAPP, BDAF, DABP, DDM, DDS.
[0097] All remaining formulations were prepared following this procedure within the following ranges. Target density, Td From 0.02g / cm 3 To 0.10g / cm 3 The monomer stoichiometric balance PMDA / PDA molar ratio is from 0.80 to 1.0. The order of monomer addition is to completely dissolve the diamine first, then add the dianhydride, or add the dianhydride first, then wait 30 seconds or 30 minutes, and then add the diamine. The molar ratio of pyridine to PMDA is 1 to 5 molar equivalents. The molar ratio of acetic anhydride to PMDA is 0.75 to 4.3 molar equivalents. Fig.23 The table in describes the formulations for a subset of samples designed with controlled molecular weight.
[0098] Here is a description of the Fig.18 and Fig.19 The processing procedures for representative polyimide aerogel samples are shown in the table. After 24 hours of gelation, the wet gel samples were removed from the molds and washed three times with ethanol at around 25°C, allowing them to stand in fresh ethanol for 24 hours each time. Some other wet gel samples were removed from the molds and washed three times with ethanol in a sealed container placed in an oven at 68°C, allowing them to stand in fresh ethanol at 68°C for 24 hours each time. The wet gels produced by either method were dried with supercritical fluid (SCF) carbon dioxide to produce polyimide aerogel monoliths. The aerogel monoliths were then stored under ambient conditions. Selected aerogel samples were heat treated at 300°C in air for 4 hours to completely convert any remaining polyamic acid groups to polyimide. For general material properties of these aerogels, see Fig.18 For their mechanical properties see Fig.19 and Fig.21 . Fig.15 The solid state of a representative polymer aerogel sample is shown. 13 C NMR, 15 N NMR, infrared (IR) and X-ray diffraction (XRD) spectroscopy.
[0099] NMR (top) and FTIR (middle) confirm the chemical structure of the polyimide. Nitrogen NMR (top right) indicates the degree of conversion of polyamide to polyimide, and a single peak around 178ppm confirms that the monomer is completely converted to polyimide. The sharp peaks in XRD (bottom) indicate crystallinity. An integrated analysis is performed to obtain the crystallinity %. We studied the effect of the amount of crystallinity: the degree of crystallinity does not correspond to mechanical strength, however, all strong samples we have measured have non-zero crystallinity.
[0100] Finally, the aerogel monolith from all previous cleaning and thermal processes was heated at 5°C / min up to 1050°C and kept at this temperature for 2 hours under flowing nitrogen (10 SCFH) to obtain the corresponding carbon aerogel monolith. For general material properties of these aerogels, see Fig. 20 For their mechanical properties see Fig. 22 . Fig.17 SEM images at two different magnifications as well as XRD and Raman spectra of representative carbon aerogel samples are shown.
[0101] Molecular weight determination
[0102] Polymer molecular weight (MW) is measured in two ways:
[0103] 1. GPC
[0104] Polyamic acid samples synthesized in DMF were diluted to 10 mg / mL with DMF and then run in a Tohsoh EcoSEC Elite GPC at 0.5 mL / min at 40° C. The molecular weight was defined using the peak elution time and a calibration curve of polystyrene standards.
[0105] 2. Rheology
[0106] Polyamic acid samples with various target molecular weights were synthesized in DMAc via controlled monomer stoichiometry (PMDA / PDA) and at different concentrations. The linear viscoelastic response of polyamic acid solutions was measured at 25°C by rheology via a cone (60 mm in diameter, 2° in slope) and plate geometry on a temperature-controlled Peltier plate. Continuous flow rheology was performed on the polymer solution at 1 rad / s to determine viscosity. The log-linear plot of reduced viscosity versus polymer concentration was linearly extrapolated to zero concentration viscosity, which defines the intrinsic viscosity of each molecular weight controlled sample. The Mark-Houwink plot was constructed by plotting the relationship between intrinsic viscosity and polymer molecular weight, where the molecular weight is derived from the Carothers equation. The Mark-Houwink parameter α was calculated to be 0.60, which is a reasonable value for polymers in good solvents.
[0107] Comparison of the expected MW from the Carother equation with the experimental GPC molecular weight results showed a highly linear relationship, with the GPC result being 0.57 times lower than the ideal expected value. This discrepancy is due to the incomplete extent of the reaction.
[0108] High stoichiometric control over the reagents results in controlled polymer molecular weight, since polymer chain length is determined by the Carothers equation 1 Predicted:
[0109]
[0110] where x n is the degree of polymerization, r is the stoichiometric ratio between A and B monomers, and p is the extent of reaction, which is assumed to be close to unity with sufficiently long reaction times. Using this equation, we can predict the number average molecular weight (Mn) of the resulting polymer based on an intentional imbalance in monomer stoichiometry, as shown in Figure 16C.
[0111] Sample preparation
[0112] Sample 1. A PMDA to PDA molar ratio of 0.90 was used to obtain a total solid (PDA + PMDA) concentration in the solvent = 0.10 g / cm 3 The prepared polyamic acid solution (see Fig.23 ). 1,4-phenylenediamine (PDA; 3.552 g) was dissolved in 100 mL of N,N-dimethylacetamide (DMAc) in a 500 mL beaker. After 15 minutes, solid pyromellitic dianhydride (PMDA; 6.448 g) was added to the solution (0.9 mol / mol PMDA / PDA). The solution was stirred overnight at room temperature using a magnetic stir bar. At the end of this period, the viscosity was measured using a rheometer.
[0113] Sample 2. A PMDA to PDA molar ratio of 0.95 was used to obtain a total solid (PDA + PMDA) concentration in the solvent = 0.10 g / cm 3 The prepared polyamic acid solution (see Fig.23 ). 1,4-phenylenediamine (PDA; 3.429 g) was dissolved in 100 mL of N,N-dimethylacetamide (DMAc) in a 500 mL beaker. After 15 minutes, solid pyromellitic dianhydride (PMDA; 6.571 g) was added to the solution (0.95 mol / mol PMDA / PDA). The solution was stirred overnight at room temperature using a magnetic stir bar. At the end of this period, the viscosity was measured using a rheometer.
[0114] Sample 3. Using a PMDA to PDA molar ratio of 0.98 with a total solids (PDA + PMDA) concentration in solvent = 0.10 g / cm 3 The prepared polyamic acid solution (see Fig.23). 1,4-phenylenediamine (PDA; 3.359 g) was dissolved in 100 mL of N,N-dimethylacetamide (DMAc) in a 500 mL beaker. After 15 minutes, solid pyromellitic dianhydride (PMDA; 6.641 g) was added to the solution (0.98 mol / mol PMDA / PDA). The solution was stirred overnight at room temperature using a magnetic stir bar. At the end of this period, the viscosity was measured using a rheometer.
[0115] Sample 4. Using a PMDA to PDA molar ratio of 0.99 with a total solids (PDA + PMDA) concentration in solvent = 0.10 g / cm 3 The prepared polyamic acid solution (see Fig.23 ). 1,4-phenylenediamine (PDA; 3.337 g) was dissolved in 100 mL of N,N-dimethylacetamide (DMAc) in a 500 mL beaker. After 15 minutes, solid pyromellitic dianhydride (PMDA; 6.663 g) was added to the solution (0.99 mol / mol PMDA / PDA). The solution was stirred overnight at room temperature using a magnetic stir bar. At the end of this period, the viscosity was measured using a rheometer.
[0116] Sample 5. Using a PMDA to PDA molar ratio of 0.80 with a total solids (PDA + PMDA) concentration in solvent = 0.050 g / cm 3 The prepared polyamic acid solution and polyimide aerogel (see Fig.23 ). 1,4-phenylenediamine (PDA; 3.826 g) was dissolved in 200 mL of N,N-dimethylacetamide (DMAc) in a 500 mL beaker. After 15 minutes, solid pyromellitic dianhydride (PMDA; 6.174 g) was added to the solution (0.80 mol / mol PMDA / PDA). The solution was stirred overnight at room temperature using a magnetic stir bar. At the end of this period, the viscosity was measured using a rheometer.
[0117] Another polyamic acid solution was prepared similarly and the viscosity was recorded ( Fig.21 ). Then, 2.4 equivalents of pyridine (5.82 g, 5.93 mL) were added to the solution. After mixing for 2 minutes, 4.3 equivalents of acetic anhydride (13.46 g, 12.46 mL) were added to the solution. The target density of the resulting sol was T d 0.046g / cm 3. The new solution was dispensed into shallow circular aluminum casting pans and the solution was allowed to gel. The casting pans were covered and allowed to age for 24 hours. The wet gel was then removed from the mold and washed three times with ethanol at about 25°C, allowing each wash to stand in fresh ethanol for 24 hours. The resulting wet gel was dried with supercritical fluid (SCF) carbon dioxide into thin polyimide aerogel monoliths, which were stored under ambient conditions. These aerogels were also subjected to three-point bending tests (results see Fig.21 ).
[0118] Sample 6. Using a PMDA to PDA molar ratio of 0.90 with a total solids (PDA + PMDA) concentration in solvent = 0.050 g / cm 3 The prepared polyamic acid solution and polyimide aerogel (see Fig.23 ). 1,4-phenylenediamine (PDA; 3.552 g) was dissolved in 200 mL of N,N-dimethylacetamide (DMAc) in a 500 mL beaker. After 15 minutes, solid pyromellitic dianhydride (PMDA; 6.448 g) was added to the solution (0.90 mol / mol PMDA / PDA). The solution was stirred overnight at room temperature using a magnetic stir bar. At the end of this period, the viscosity was measured using a rheometer.
[0119] Another polyamic acid solution was prepared similarly and the viscosity was recorded ( Fig.21 ). Then, 2.4 equivalents of pyridine (5.82 g, 5.93 mL) were added to the solution. After mixing for 2 minutes, 4.3 equivalents of acetic anhydride (13.46 g, 12.46 mL) were added to the solution. The target density of the resulting sol was T d 0.046g / cm 3 . The new solution was dispensed into shallow circular aluminum casting pans and the solution was allowed to gel. The casting pans were covered and allowed to age for 24 hours. The wet gel was then removed from the mold and washed three times with ethanol at about 25°C, allowing each wash to stand in fresh ethanol for 24 hours. The resulting wet gel was dried with supercritical fluid (SCF) carbon dioxide into thin polyimide aerogel monoliths, which were stored under ambient conditions. These aerogels were also subjected to three-point bending tests (results see Fig.21 ).
[0120] Sample 7. A PMDA to PDA molar ratio of 0.95 was used to obtain a total solids (PDA + PMDA) concentration in solvent = 0.050 g / cm 3 The prepared polyamic acid solution and polyimide aerogel (see Fig.23). 1,4-phenylenediamine (PDA; 3.429 g) was dissolved in 200 mL of N,N-dimethylacetamide (DMAc) in a 500 mL beaker. After 15 minutes, solid pyromellitic dianhydride (PMDA; 6.571 g) was added to the solution (0.95 mol / mol PMDA / PDA). The solution was stirred overnight at room temperature using a magnetic stir bar. At the end of this period, the viscosity was measured using a rheometer.
[0121] Another polyamic acid solution was prepared similarly and the viscosity was recorded ( Fig.21 ). Then, 2.4 equivalents of pyridine (5.82 g, 5.93 mL) were added to the solution. After mixing for 2 minutes, 4.3 equivalents of acetic anhydride (13.46 g, 12.46 mL) were added to the solution. The target density of the resulting sol was T d 0.046g / cm 3 . The new solution was dispensed into shallow circular aluminum casting pans and the solution was allowed to gel. The casting pans were covered and allowed to age for 24 hours. The wet gel was then removed from the mold and washed three times with ethanol at about 25°C, allowing each wash to stand in fresh ethanol for 24 hours. The resulting wet gel was dried with supercritical fluid (SCF) carbon dioxide into thin polyimide aerogel monoliths, which were stored under ambient conditions. These aerogels were also subjected to three-point bending tests (results see Fig.21 ).
[0122] Sample 8. A PMDA to PDA molar ratio of 0.98 was used to obtain a total solids (PDA + PMDA) concentration in solvent = 0.050 g / cm 3 The prepared polyamic acid solution and polyimide aerogel (see Fig.23 ). 1,4-phenylenediamine (PDA; 3.359 g) was dissolved in 200 mL of N,N-dimethylacetamide (DMAc) in a 500 mL beaker. After 15 minutes, solid pyromellitic dianhydride (PMDA; 6.641 g) was added to the solution (0.98 mol / mol PMDA / PDA). The solution was stirred overnight at room temperature using a magnetic stir bar. At the end of this period, the viscosity was measured using a rheometer.
[0123] Another polyamic acid solution was prepared similarly and the viscosity was recorded ( Fig.21 ). Then, 2.4 equivalents of pyridine (5.82 g, 5.93 mL) were added to the solution. After mixing for 2 minutes, 4.3 equivalents of acetic anhydride (13.46 g, 12.46 mL) were added to the solution. The target density of the resulting sol was T d 0.046g / cm 3. The new solution was dispensed into shallow circular aluminum casting pans and the solution was allowed to gel. The casting pans were covered and allowed to age for 24 hours. The wet gel was then removed from the mold and washed three times with ethanol at about 25°C, allowing each wash to stand in fresh ethanol for 24 hours. The resulting wet gel was dried with supercritical fluid (SCF) carbon dioxide into thin polyimide aerogel monoliths, which were stored under ambient conditions. These aerogels were also subjected to three-point bending tests (results see Fig.21 ).
[0124] Sample 9. A PMDA to PDA molar ratio of 0.99 was used to obtain a total solids (PDA + PMDA) concentration in solvent = 0.050 g / cm 3 The prepared polyamic acid solution and polyimide aerogel (see Fig.23 ). 1,4-phenylenediamine (PDA; 3.337 g) was dissolved in 200 mL of N,N-dimethylacetamide (DMAc) in a 500 mL beaker. After 15 minutes, solid pyromellitic dianhydride (PMDA; 6.663 g) was added to the solution (0.99 mol / mol PMDA / PDA). The solution was stirred overnight at room temperature using a magnetic stir bar. At the end of this period, the viscosity was measured using a rheometer.
[0125] Another polyamic acid solution was prepared similarly and the viscosity was recorded ( Fig.21 ). Then, 2.4 equivalents of pyridine (5.82 g, 5.93 mL) were added to the solution. After mixing for 2 minutes, 4.3 equivalents of acetic anhydride (13.46 g, 12.46 mL) were added to the solution. The target density of the resulting sol was T d 0.046g / cm 3 . The new solution was dispensed into shallow circular aluminum casting pans and the solution was allowed to gel. The casting pans were covered and allowed to age for 24 hours. The wet gel was then removed from the mold and washed three times with ethanol at about 25°C, allowing each wash to stand in fresh ethanol for 24 hours. The resulting wet gel was dried with supercritical fluid (SCF) carbon dioxide into thin polyimide aerogel monoliths, which were stored under ambient conditions. These aerogels were also subjected to three-point bending tests (results see Fig.21 ).
[0126] Sample 10. A PMDA to PDA molar ratio of 0.995 was used to obtain a total solids (PDA + PMDA) concentration in solvent = 0.050 g / cm 3 The prepared polyamic acid solution and polyimide aerogel (see Fig.23). 1,4-phenylenediamine (PDA; 3.337 g) was dissolved in 200 mL of N,N-dimethylacetamide (DMAc) in a 500 mL beaker. After 15 minutes, solid pyromellitic dianhydride (PMDA; 6.674 g) was added to the solution (0.995 mol / mol PMDA / PDA). The solution was stirred overnight at room temperature using a magnetic stir bar. At the end of this period, the viscosity was measured using a rheometer.
[0127] Another polyamic acid solution was prepared similarly and the viscosity was recorded ( Fig.21 ). Then, 2.4 equivalents of pyridine (5.82 g, 5.93 mL) were added to the solution. After mixing for 2 minutes, 4.3 equivalents of acetic anhydride (13.46 g, 12.46 mL) were added to the solution. The target density of the resulting sol was T d 0.046g / cm 3 . The new solution was dispensed into shallow circular aluminum casting pans and the solution was allowed to gel. The casting pans were covered and allowed to age for 24 hours. The wet gel was then removed from the mold and washed three times with ethanol at about 25°C, allowing each wash to stand in fresh ethanol for 24 hours. The resulting wet gel was dried with supercritical fluid (SCF) carbon dioxide into thin polyimide aerogel monoliths, which were stored under ambient conditions. These aerogels were also subjected to three-point bending tests (results see Fig.21 ).
[0128] Sample 11. A PMDA to PDA molar ratio of 0.80 was used to obtain a total solids (PDA + PMDA) concentration in the solvent = 0.020 g / cm 3 The prepared polyamic acid solution (see Fig.23 ). 1,4-phenylenediamine (PDA; 3.826 g) was dissolved in 500 mL of N,N-dimethylacetamide (DMAc) in a 1000 mL beaker. After 15 minutes, solid pyromellitic dianhydride (PMDA; 6.174 g) was added to the solution (0.80 mol / mol PMDA / PDA). The solution was stirred overnight at room temperature using a magnetic stir bar. At the end of this period, the viscosity was measured using a rheometer.
[0129] Sample 12. A PMDA to PDA molar ratio of 0.90 was used to obtain a total solids (PDA + PMDA) concentration in solvent = 0.020 g / cm 3 The prepared polyamic acid solution (see Fig.23). 1,4-phenylenediamine (PDA; 3.552 g) was dissolved in 500 mL of N,N-dimethylacetamide (DMAc) in a 1000 mL beaker. After 15 minutes, solid pyromellitic dianhydride (PMDA; 6.448 g) was added to the solution (0.90 mol / mol PMDA / PDA). The solution was stirred overnight at room temperature using a magnetic stir bar. At the end of this period, the viscosity was measured using a rheometer.
[0130] Sample 13. A PMDA to PDA molar ratio of 0.95 was used to obtain a total solids (PDA + PMDA) concentration in solvent = 0.020 g / cm 3 The prepared polyamic acid solution (see Fig.23 ). 1,4-phenylenediamine (PDA; 3.429 g) was dissolved in 500 mL of N,N-dimethylacetamide (DMAc) in a 1000 mL beaker. After 15 minutes, solid pyromellitic dianhydride (PMDA; 6.571 g) was added to the solution (0.95 mol / mol PMDA / PDA). The solution was stirred overnight at room temperature using a magnetic stir bar. At the end of this period, the viscosity was measured using a rheometer.
[0131] Sample 14. A PMDA to PDA molar ratio of 0.98 was used to obtain a total solids (PDA + PMDA) concentration in solvent = 0.020 g / cm 3 The prepared polyamic acid solution (see Fig.23 ). 1,4-phenylenediamine (PDA; 3.359 g) was dissolved in 500 mL of N,N-dimethylacetamide (DMAc) in a 1000 mL beaker. After 15 minutes, solid pyromellitic dianhydride (PMDA; 6.641 g) was added to the solution (0.98 mol / mol PMDA / PDA). The solution was stirred overnight at room temperature using a magnetic stir bar. At the end of this period, the viscosity was measured using a rheometer.
[0132] Sample 15. A PMDA to PDA molar ratio of 0.99 was used to obtain a total solids (PDA + PMDA) concentration in solvent = 0.020 g / cm 3 The prepared polyamic acid solution and polyimide aerogel (see Fig.23 ). 1,4-phenylenediamine (PDA; 3.337 g) was dissolved in 500 mL of N,N-dimethylacetamide (DMAc) in a 1000 mL beaker. After 15 minutes, solid pyromellitic dianhydride (PMDA; 6.663 g) was added to the solution (0.99 mol / mol PMDA / PDA). The solution was stirred overnight at room temperature using a magnetic stir bar. At the end of this period, the viscosity was measured using a rheometer.
[0133] Sample 16. Total solids (PDA + PMDA) concentration in solvent = 0.010 g / cm 3 and a polyamic acid solution prepared with a PMDA to PDA molar ratio of 0.80 (see Fig.23 After stirring for 24 hours, 2.00 g of the polyamic acid solution of sample 11 was diluted with 1.96 g of DMAc to obtain a total solid concentration of 0.010 g / cm 3 The final solution was obtained by mixing the sol with a 4% ethanol solution. This new solution was referred to as Sample 16. The viscosity of the sol was immediately measured using a rheometer. No gel was prepared from Sample 16.
[0134] Sample 17. Total solids (PDA + PMDA) concentration in solvent = 0.010 g / cm 3 and a polyamic acid solution prepared with a PMDA to PDA molar ratio of 0.90 (see Fig.23 After stirring for 24 hours, 2.00 g of the polyamic acid solution of sample 12 was diluted with 1.96 g of DMAc to obtain a total solid concentration of 0.010 g / cm 3 This new solution is called Sample 17. The viscosity of the sol was immediately measured using a rheometer. No gel was prepared from Sample 17.
[0135] Sample 18. Total solids (PDA + PMDA) concentration in solvent = 0.010 g / cm 3 and a polyamic acid solution prepared with a PMDA to PDA molar ratio of 0.95 (see Fig.23 After stirring for 24 hours, 2.00 g of the polyamic acid solution of sample 13 was diluted with 1.96 g of DMAc to obtain a total solid concentration of 0.010 g / cm 3 The final solution was prepared by mixing the sol with a flowmeter. This new solution was designated as Sample 18. The viscosity of the sol was immediately measured using a rheometer. No gel was prepared from Sample 18.
[0136] Sample 19. Total solids (PDA + PMDA) concentration in solvent = 0.010 g / cm 3 and a polyamic acid solution prepared with a PMDA to PDA molar ratio of 0.98 (see Fig.23 After stirring for 24 hours, 2.00 g of the polyamic acid solution of sample 14 was diluted with 1.96 g of DMAc to obtain a total solid concentration of 0.010 g / cm 3 The final solution was prepared by mixing the sol with a flowmeter. This new solution was called Sample 19. The viscosity of the sol was immediately measured using a rheometer. No gel was prepared from Sample 19.
[0137] Sample 20. Total solids (PDA + PMDA) concentration in solvent = 0.010 g / cm 3and a polyamic acid solution prepared with a PMDA to PDA molar ratio of 0.99 (see Fig.23 After stirring for 24 hours, 2.00 g of the polyamic acid solution of sample 15 was diluted with 1.96 g of DMAc to obtain a total solid concentration of 0.01 g / cm 3 This new solution is called Sample 20. The viscosity of the sol was immediately measured using a rheometer. No gel was prepared from Sample 20.
[0138] Sample 21. Total solids (PDA + PMDA) concentration in solvent = 0.050 g / cm using a PMDA to PDA molar ratio of 0.99 3 Attempted preparation of polyamic acid solution and polyimide aerogel of - Difference from Sample 9: Here the reaction mixture is first started by dissolving the dianhydride (see Fig.23 ). Pyromellitic dianhydride (PMDA; 6.663 g) was dissolved in 200 mL N, N-dimethylacetamide (DMAc) in a 500 mL beaker. After 30 minutes, solid 1,4-phenylenediamine (PDA; 3.337 g) was added to the solution (0.99 mol / mol PMDA / PDA). The solution was stirred overnight at room temperature using a magnetic stirring bar. At the end of this period, the viscosity was measured with a rheometer, and then 2.4 equivalents of pyridine (5.82 g, 5.93 mL) were added to the solution. After mixing for 2 minutes, 4.3 equivalents of acetic anhydride (13.46 g, 12.46 mL) were added to the solution. The target density T of the resulting sol was 1.34 g. d 0.05g / cm 3 . The new solution was divided into shallow circular aluminum casting pans and the solution was allowed to gel. The casting pans were covered and allowed to age for 24 hours. After the 24-hour aging period, the wet gel from Sample 21 was found to be extremely brittle and had broken into pieces. The wet gel pieces could not be removed from the mold and were discarded. Since the resulting wet gel could not be transferred for supercritical fluid (SCF) carbon dioxide drying, Sample 21 did not produce a polyimide aerogel monolith.
[0139] application
[0140] One or more of the above embodiments can be used in a variety of technical applications. Some embodiments can be used as: bulletproof barriers; self-supporting, low-density, high thermal insulation, hydrophobic housings, such as for wireless communication devices (e.g., from 1 gigahertz (GHz) to 5 terahertz (THz) in 5G and 6G communication frequencies); as thermal and structural insulation in air vehicles (aircraft, missiles, drones); thermal / humidity nose cone protection for air vehicles that is also transparent to communication frequencies; substrates of a second phase disposed in the pores of the aerogel; mechanically strong and dimensionally stable plates that may or may not include a second phase (e.g., battery cathode material or anode material); mechanically strong and dimensionally stable carbonized plates that may or may not include a second phase (e.g., to form a collector-free rechargeable battery cathode and / or anode). Some embodiments can be used for mechanically tough and / or high fracture toughness thermal insulation panels (e.g., having a thermal conductivity of less than 40 mW / m-Kelvin). In some examples, materials used in this context may also be processed to include or contain a hydrophobe such that the mechanically tough insulation panel is hydrophobic.
[0141] aspect
[0142] To better illustrate the methods and apparatus disclosed herein, a non-limiting list of aspects is provided here:
[0143] Aspect 1. An aerogel composition comprising: a polyimide matrix composed of linear polyimide molecules, wherein the polyimide matrix has a nanoporous structure; wherein the linear polyimide molecules comprise a molecular weight greater than 10,000 g / mol; and wherein the aerogel composition has a compressive yield stress greater than 1.5 MPa when the bulk density is between 0.05 and 0.35 g / cm3.
[0144] Aspect 2. The aerogel composition of aspect 1, wherein the linear polyimide molecules comprise a molecular weight greater than 15,000 g / mol and less than 200,000 g / mol.
[0145] Aspect 3. The aerogel composition of aspect 1, wherein the aerogel composition comprises a bulk density between 0.05 and 0.20 g / cm3.
[0146] Aspect 4. The aerogel composition according to aspect 1, wherein the aerogel composition has a compressive yield stress greater than 1.5 MPa when the bulk density is between 0.05 and 0.20 g / cm3.
[0147] Aspect 5. The aerogel composition according to aspect 2, wherein the aerogel composition has a flexural strength greater than 0.4 MPa when the molecular weight is greater than 10,000 g / mol.
[0148] Aspect 6. The aerogel composition of aspect 1, wherein the polyimide matrix comprises a percent crystallinity greater than zero.
[0149] Aspect 7. The aerogel composition of aspect 1, wherein the polyimide matrix comprises a percent crystallinity greater than 5%.
[0150] Aspect 8. The aerogel composition of aspect 1, wherein the polyimide matrix comprises a percent crystallinity between 5% and 10%.
[0151] Aspect 9. An aerogel composition comprising: a polyimide matrix composed of linear polyimide molecules, the polyimide matrix having a nanoporous structure; wherein the linear polyimide molecules include a monomer length of N, wherein 30≤N≤650; and the aerogel composition has a density-normalized compression modulus greater than 13 J / g.
[0152] Aspect 10. The aerogel composition of aspect 9, wherein the linear polyimide molecule comprises a monomer length of N, wherein 50≤N≤400.
[0153] Aspect 11. The aerogel composition of aspect 9, wherein the aerogel composition comprises a density normalized compression modulus greater than 100 J / g.
[0154] Aspect 12. The aerogel composition of aspect 9, wherein the aerogel composition has a bulk density between 0.05 and 0.80 g / cm3.
[0155] Aspect 13. The aerogel composition of aspect 9, wherein the polyimide matrix comprises a percent crystallinity greater than zero.
[0156] Aspect 14. The aerogel composition of aspect 9, wherein the polyimide matrix comprises a percent crystallinity greater than 5%.
[0157] Aspect 15. The aerogel composition of aspect 9, wherein the polyimide matrix comprises a percent crystallinity between 5% and 60%.
[0158] Aspect 16. An aerogel composition comprising: a polyimide matrix composed of linear polyimide molecules, the polyimide matrix having a nanoporous structure; wherein the linear polyimide molecules comprise a molecular weight greater than 10,000 g / mol; and the aerogel composition has a flexural strength greater than 0.4 MPa.
[0159] Aspect 17. The aerogel composition of aspect 16, wherein the aerogel composition has a bulk density between 0.05 and 0.80 g / cm3.
[0160] Aspect 18. The aerogel composition of aspect 16, wherein the polyimide matrix comprises a percent crystallinity greater than zero.
[0161] Aspect 19. A method of forming an aerogel composition, comprising: polymerizing a dianhydride and a diamine to form a linear molecular polyimide matrix having a molecular weight greater than 10,000 g / mol; gelling the linear molecular polyimide matrix without crosslinking to form a wet gel; and removing the solvent from the wet gel to form a polyimide aerogel.
[0162] Aspect 20. The method of aspect 19, wherein polymerizing the dianhydride and the diamine comprises polymerizing PMDA and PDA.
[0163] Aspect 21. The method of aspect 19, wherein polymerizing the dianhydride and the diamine comprises polymerizing a dianhydride selected from the group consisting of BTDA, BPADA, BPDA, ODPA, DSDA, and 6FDA.
[0164] Aspect 22. The method of aspect 19, wherein polymerizing the dianhydride and the diamine comprises polymerizing a diamine selected from the group consisting of meta-PDA, ODA, BAPP, BDAF, DABP, DDM, and DDS.
[0165] Aspect 23. The method of aspect 19, further comprising dissolving the diamine in a certain amount of pyridine before polymerization to obtain a solution with a solid solution percentage greater than 0.05 g / cm3.
[0166] Aspect 24. The method of aspect 19, further comprising annealing the wet gel at 68° C. before removing the solvent from the wet gel.
[0167] Aspect 25. The method of aspect 24, further comprising heat treating the polyimide aerogel at 300° C. for about 4 hours.
[0168] Aspect 26. The method of aspect 19, further comprising carbonizing the polyimide aerogel.
[0169] in conclusion
[0170] Although an overview of the inventive subject matter has been described with reference to specific exemplary embodiments, various modifications and changes may be made to these embodiments without departing from the broader scope of the embodiments of the present disclosure. Such embodiments of the inventive subject matter may be referred to herein, individually or collectively, by the term "invention", which is merely for convenience and is not intended to actively limit the scope of the present application to any single disclosure or inventive concept (if more than one invention is actually disclosed).
[0171] The embodiments illustrated herein are described in sufficient detail to enable those skilled in the art to practice the disclosed teachings. Other embodiments may be used and derived therefrom, such that structural and logical substitutions and changes may be made without departing from the scope of the present disclosure. The detailed description should therefore not be interpreted in a limiting sense, and the scope of the various embodiments is limited only by the appended claims together with the full scope of equivalents to which such claims are entitled.
[0172] As used herein, the term "or" may be interpreted in an inclusive or exclusive sense. In addition, multiple instances may be provided as a single instance for the resources, operations, or structures described herein. In addition, the boundaries between various resources, operations, modules, engines, and data stores are arbitrary to some extent, and specific operations are described in the context of specific illustrative configurations. Other functional allocations are contemplated, and these functional allocations may fall within the scope of various embodiments of the present disclosure. In general, the structures and functions presented as separate resources in the example configurations may be implemented as combined structures or resources. Similarly, the structures and functions presented as single resources may be implemented as separate resources. These and other changes, modifications, additions, and improvements all fall within the scope of the embodiments of the present disclosure represented by the appended claims. Therefore, the specification and the accompanying drawings are considered to be illustrative rather than restrictive.
[0173] For purposes of explanation, the foregoing description has been described with reference to specific example embodiments. However, the above illustrative discussion is not intended to be comprehensive or to limit possible example embodiments to the precise form disclosed. Many modifications and variations are possible in light of the above teachings. The example embodiments are selected and described in order to best explain the principles involved and their practical application, so as to enable those skilled in the art to best utilize the various example embodiments with various modifications to suit specific intended uses.
[0174] It will also be understood that although the terms "first", "second", etc. may be used herein to describe various elements, these elements should not be limited to these terms. These terms are only used to distinguish one element from another element. For example, without departing from the scope of the exemplary embodiments of the present invention, a first contact may be referred to as a second contact, and similarly, a second contact may be referred to as a first contact. Both the first contact and the second contact are contacts, but not the same contact.
[0175] The terms used herein in describing the exemplary embodiments are only for the purpose of describing the specific exemplary embodiments and are not intended to be limiting. As used in the description of the exemplary embodiments and the accompanying examples, the singular forms "a", "an", and "said" are also intended to include the plural forms unless the context clearly indicates otherwise. It will also be understood that the term "and / or" as used herein refers to and encompasses any and all possible combinations of one or more of the associated listed items. It should also be understood that the terms "comprises" and / or "comprising", when used in this specification, specify the presence of stated features, wholes, steps, operations, elements and / or parts, but do not exclude the presence or addition of one or more other features, wholes, steps, operations, element parts and / or groups thereof.
[0176] As used herein, the term "if" may be interpreted to mean "at the time of," "after," or "in response to determining," or "in response to detecting," depending on the context. Similarly, the term "if it is determined" or "if [the condition or event] is detected" may be interpreted to mean "after determining," or "in response to determining," or "after detecting [the condition or event]," or "in response to detecting [the condition or event]," depending on the context.
Claims
1. An aerogel composition comprising: A polyimide matrix composed of linear polyimide molecules, wherein the polyimide matrix has a nanoporous structure; wherein the linear polyimide molecules comprise a molecular weight greater than 10,000 g / mol; and The aerogel composition has a bulk density of 0.05 to 0.35 g / cm 3 When between, it has a compressive yield stress greater than 1.5MPa.
2. The aerogel composition of claim 1, wherein the linear polyimide molecules comprise a molecular weight greater than 15,000 g / mol and less than 200,000 g / mol.
3. The aerogel composition of claim 1, wherein the aerogel composition comprises 0.05 to 0.20 g / cm 3 The packing density between.
4. The aerogel composition according to claim 1, wherein the aerogel composition has a bulk density of 0.05 to 0.20 g / cm 3 When between, it has a compressive yield stress greater than 1.5MPa.
5. The aerogel composition of claim 2, wherein the aerogel composition has a flexural strength greater than 0.4 MPa when the molecular weight is greater than 10,000 g / mol.
6. The aerogel composition of claim 1, wherein the polyimide matrix comprises a percent crystallinity greater than zero.
7. The aerogel composition of claim 1, wherein the polyimide matrix comprises a percent crystallinity greater than 5%.
8. The aerogel composition of claim 1, wherein the polyimide matrix comprises a percent crystallinity between 5% and 10%.
9. An aerogel composition comprising: A polyimide matrix composed of linear polyimide molecules, wherein the polyimide matrix has a nanoporous structure; wherein the linear polyimide molecule comprises a monomer length of N, wherein 30≤N≤650; and The aerogel composition has a density normalized compression modulus greater than 13 J / g.
10. The aerogel composition of claim 9, wherein the linear polyimide molecule comprises a monomer length of N, wherein 50≤N≤400.
11. The aerogel composition of claim 9, wherein the aerogel composition comprises a density normalized compression modulus greater than 100 J / g.
12. The aerogel composition of claim 9, wherein the aerogel composition has a relative humidity of 0.05 to 0.80 g / cm 3 The packing density between.
13. The aerogel composition of claim 9, wherein the polyimide matrix comprises a percent crystallinity greater than zero.
14. The aerogel composition of claim 9, wherein the polyimide matrix comprises a percent crystallinity greater than 5%.
15. The aerogel composition of claim 9, wherein the polyimide matrix comprises a percent crystallinity between 5% and 60%.
16. An aerogel composition comprising: A polyimide matrix composed of linear polyimide molecules, wherein the polyimide matrix has a nanoporous structure; wherein the linear polyimide molecules comprise a molecular weight greater than 10,000 g / mol; and The aerogel composition has a flexural strength greater than 0.4 MPa.
17. The aerogel composition of claim 16, wherein the aerogel composition has a relative humidity of 0.05 to 0.80 g / cm 3 The packing density between.
18. The aerogel composition of claim 16, wherein the polyimide matrix comprises a percent crystallinity greater than zero.
19. A method of forming an aerogel composition, comprising: polymerizing the dianhydride and the diamine to form a linear molecular polyimide matrix having a molecular weight greater than 10,000 g / mol; allowing the linear molecular polyimide matrix to gel without crosslinking to form a wet gel; as well as The solvent is removed from the wet gel to form a polyimide aerogel.
20. The method of claim 19, wherein polymerizing the dianhydride and the diamine comprises polymerizing PMDA and PDA.
21. The method of claim 19, wherein polymerizing the dianhydride and the diamine comprises polymerizing a dianhydride selected from the group consisting of BTDA, BPADA, BPDA, ODPA, DSDA, and 6FDA.
22. The method of claim 19, wherein polymerizing the dianhydride and the diamine comprises polymerizing a diamine selected from the group consisting of meta-PDA, ODA, BAPP, BDAF, DABP, DDM, DDS.
23. The method of claim 19, further comprising dissolving the diamine in an amount of pyridine prior to polymerization to obtain a solid solution percentage greater than 0.05 g / cm 3 of solution.
24. The method of claim 19, further comprising annealing the wet gel at 68°C before removing the solvent from the wet gel.
25. The method of claim 24, further comprising heat treating the polyimide aerogel at 300°C for about 4 hours.
26. The method of claim 19, further comprising carbonizing the polyimide aerogel.
Citation Information
Patent Citations
Carbon aerogel-based electrode materials and methods of manufacture thereof
US20200269207A1
Process for forming transparent aerogel insulating arrays
US4610863A
Method for producing metal oxide aerogels having densities less than 0.02 g / cc
US5275796A
Method for making monolithic metal oxide aerogels
US5395805A
Method of low pressure and / or evaporative drying of aerogel
US5420168A